(untitled) (ACME, 2024)
The study of the epistolary report elapsed between Francesco Arcangeli and Vittorio Sereni, contributes to specify some cultural and emotive characteristics of the two intellectuals’ personalities. In more than thirty years of frank and deep dialogue, capable of through the distressing atmosphere of the fascism already in decline, the drama of the world war and the rebirth, at least apparent, of the country, emerge, letter by letter, the continuous loyalty of the two corresponding – despite their diversity of opinion, both in literary and figurative/pictorial field- to the reasons of their own subjectivity, in a honest, tiring and lonely distancing from every convenience choice that wouldn’t be participated, and then morally experienced, with deep personal belief.